Pediatric patient with diagnosis of extra osseous Ewing’s sarcoma of the tongue: case report - CHAPARRO,Neira (2018)
ABSTRACT Ewing’s sarcoma is a malignant tumor that arises mainly from bone tissue, so that its extra-osseous presentation is not very common and even more unusual, in the soft tissues of the oral cavity. The objective of this case was to describe the clinical characteristics of an extra-osseous Ewing’s Sarcoma of the tongue in a pediatric patient. An 11-year-old male school patient, who attended an oral medicine consultation referring a volume increase in the tongue. Intraorally, a tumoral lesion was observed on the left lateral edge of the tongue, indurated, with the same color of the mucosa with ulcerated areas, well defined edges and symptomatic on palpation, with an approximate size of 2.5 cm. A cervical and maxillofacial MRI was indicated, observing a partially delimited hyperintense and non-infiltrating lesion in the described area. An incisional biopsy was performed with histopathological diagnosis of malignant neoplasm of blue round cells, theCD99 marker was found to be positive in the immunohistochemical study and was key to the definitive diagnosis of this tumor. A thoraco-abdomino-pelvic tomography was requested by the Pediatric Oncology service, as well as biopsy and aspiration of bone marrow, in which no neoplastic infiltrations were evidenced. After four cycles of chemotherapy, total removal of the lesion was performed with a consecutive histopathological study of the surgical piece, indicating free edges of the lesion. Ewing’s sarcoma is a tumor with aggressive behavior, so this case represents a finding of clinical and epidemiological relevance, both due to its extra-osseous appearance and its unusual behavior.